Gastrin‐releasing peptide receptor (GRPr) promotes EMT, growth, and invasion in canine prostate cancer. Issue 9 (4th March 2016) - Elshafae, Said M.; Hassan, Bardes B.; Supsavhad, Wachiraphan; Dirksen, Wessel P.; Camiener, Rachael Y.; Ding, Haiming; Tweedle, Michael F.; Rosol, Thomas J.
Abstract : BACKGROUND: The gastrin‐releasing peptide receptor (GRPr) is upregulated in early and late‐stage human prostate cancer (PCa) and other solid tumors of the mammary gland, lung, head and neck, colon, uterus, ovary, and kidney. However, little is known about its role in prostate cancer. This study examined the effects of a heterologous GRPr agonist, bombesin (BBN), on growth, motility, morphology, gene expression, and tumor phenotype of an osteoblastic canine prostate cancer cell line (Ace‐1) in vitro and in vivo. METHODS: The Ace‐1 cells were stably transfected with the human GRPr and tumor cells were grown in vitro and as subcutaneous and intratibial tumors in nude mice. The effect of BBN was measured on cell proliferation, cell migration, tumor growth (using bioluminescence), tumor cell morphology, bone tumor phenotype, and epithelial‐mesenchymal transition (EMT) and metastasis gene expression (quantitative RT‐PCR). GRPr mRNA expression was measured in primary canine prostate cancers and normal prostate glands. RESULTS: Bombesin (BBN) increased tumor cell proliferation and migration in vitro and tumor growth and invasion in vivo. BBN upregulated epithelial‐to‐mesenchymal transition (EMT) markers ( TWIST, SNAIL, and SLUG mRNA) and downregulated epithelial markers ( E‐cadherin and β‐catenin mRNA), and modified tumor cell morphology to a spindle cell phenotype. Blockade of GRPr upregulated E‐cadherin and downregulated VIMENTIN and SNAIL mRNA. BBN altered the in vivo tumor phenotype in bone from an osteoblastic to osteolytic phenotype. Primary canine prostate cancers had increased GRPr mRNA expression compared to normal prostates. CONCLUSION: These data demonstrated that the GRPr is important in prostate cancer growth and progression and targeting GRPr may be a promising strategy for treatment of prostate cancer. Prostate 76:796–809, 2016 . © 2016 Wiley Periodicals, Inc.